The influence of clinical experience and gender in the manual application of torque on screws of implant-supported prosthesis - Silva, Ebele Adaobi; Sousa, Cecília Alves de; Alves Rezende, Maria Cristina Rosifini; Santos, Paulo Henrique dos; Assunção, Wirley Gonçalves (ARCHIVES OF HEALTH INVESTIGATION, 2018)
Compare with the torque value recommended by the manufacturer, the values of maximum closing torques generated by volunteers of the male and female gender, with and without experience in implant-prosthesis, for tightening the screw UCLA abutment retention. The hypotheses tested were that the greatest experience in the field would not influence the value of the applied torque, as there would be no difference between volunteers from different genders. In this way, 266 volunteers were classified according to their expertise in pre-clinical (PC), clinical (C) and professional (P). Were placed seated, simulating normal forward work position in front a digital torque meter. A specimen composed of an external hex implant embedded in modified polyester resin, a metal crown and its retaining screw was attached on torque meter. The participants were provided with directions to tighten the abutment retaining screw by using a manual torque driver and apply full force in one movement of rotation. The professional group achieved the highest mean manual torque (15.80 N / cm); males (14.96 N/cm) scores a higher than females (02.11 N/cm). They could not reach the torque value recommended by the manufacturer. Thus, the factors that influence the manual application of torque include the level of clinical experience and the physical strength of the operator. The conclusion is that the use of a calibrated mechanical driver torque is essential to apply a suitable and controlled torque value and capable of promoting a proper preload and maintaining the screwed joint for long periods. Descriptors: Dental Implants; Dental Prosthesis, Implant-Supported; Stress, Mechanical.